التلوث الإشعاعي باليورانيوم المستنفذ في بناية برج التحرير - حيدر احمد حسن; محمود محمد حسين; احمد شوقي محمد; اسعد جميل زغير (Journal of Madenat Alelem University College, 2011)
The research plan included assessment of the radioactivity of the AL-Tahreer Tower Building (the Turkish restaurant recent ) through direct measurements and sampling of soil for the four floors (1th,2th,3th,4th) of the building, which contains fourteen floor in addition to the basement, by using portable radiation detection equipments to know the increasing in the levels of exposure and contamination resulting from the bombing a AL-Tahreer Tower building by depleted uranium bullets, the results of radiological surveys by using the portable contamination radiation detection (CAB) indicated readings of contaminated soil reached to 60 c/sec, and parts of shells of depleted uranium reached to 90 c/ sec , while the natural contamination rate in the area is ( 0.5 c/sec), the natural exposure rate in the area is 9 µR / hr but the higher exposure rate reached to 60 µR / hr when the device ( Ludlum) putting on the contaminated regions(distance about 0.5 cm). The radiological analyses of the collected soil samples were done in the laboratory of the center of Radiological Researches in the Ministry of sciences and Technology by using gamma spectrometry( which contains High- purity Germanium Detector) with a efficiency of 40% and resolution 2 keV for Energy, 1.33Mev,collection,preparations and tests of soil samples were all done according to IAEA.The normal concentration for Th-234 and Pa-234m in the soil samples taken from areas near to the building (can consider as background radiation region) is in range 41 Bq /Kg for Th-234,and nil for pa-234m ,while higher concentration of Th-234 in contaminated soil is 1194 Bq/Kg,and 1664Bq/kg for pa-234m which is a clear indication of the presence of high concentrations an isotope of uranium-238 as they are supposed to be in equilibrium radiation. The major aim of this study include removal the contaminated regions in the building, to protect the population and the environment from the effect of radiological contamination which resulted from using Depleted Uranium bullets in this building.